New Directions for Competencies in Counsellor Education - Marks, Stephen E.; Kahn, Sharon E.; Tolsma, Robert J. (Canadian Journal of Counselling and Psychotherapy, 2012)
The use of competencies in counsellor education has been complicated by lack of agreement on the most important areas of counsellor competence and the categories into which competencies may be placed. In addition there is no agreement as to the form in which the competency statements themselves are written. The adoption of a standard category system and a standard format for writing competency statements is recommended to improve the research and implementation of competencies in counsellor education.